Risk factor for Mycobacterium leprae detection in household contacts with leprosy patients: a study in Papua, East Indonesia (Medical Journal of Indonesia, 2020)
BACKGROUND In the era of leprosy eradication, Jayapura is still one of the biggest leprosy pockets in Papua, Indonesia. The trend for leprosy case detection rate has remained relatively stable over recent years. This study was aimed to detect Mycobacterium leprae in household contacts and to evaluate the associated factors with the detection. METHODS This cross-sectional study recruited household contacts of leprosy patients who were diagnosed consecutively from March to August 2015 in Hamadi Point of Care, Jayapura. The leprosy patients were diagnosed using polymerase chain reaction (PCR). For each leprosy patient, up to four household contacts that had no symptom were included. Every household contact received screening through DNA detection of M. leprae extracted from nasal swab specimens and examined using PCR. Factors for bacteria detection included intensity, time duration and number of contacts living together in the same house, and random blood glucose levels were evaluated. Bivariate analysis was used to associate them with M. leprae detection in household contacts. RESULTS From 107 household contacts of 35 patients who had leprosy, M. leprae was detected in 19.6%. Household contacts with leprosy patients for >1 year was a risk factor for detection (OR = 12.45; 95% CI = 1.595–97.20; p = 0.002). Blood glucose (p = 0.444), ethnic (p = 0.456), sleeping proximity to leprosy case (p = 0.468) and relatives (p = 0.518) give no effect to M. leprae detection in household contacts. CONCLUSIONS Among the various risk factors studied, duration of living together with the patient significantly increased the risk of M. leprae transmission.